Гистерезисные нестационарные нелинейности - Борздыко, В.И. (Український математичний журнал, 2008)
Отримано достатні умови, за яких оператор - змінний гістерон, що описує за схемою Красносельського - Покровського нестаціонарну гістерезисну нелінійність, характеристики якої змінюються під впливом зовнішніх сил, є визначеним для входів із класу функцій H1[t0, T], що задовольняють на відрізку [t0, T] умову Ліпшиця. We consider an operator (variable hysteron) used to describe a nonstationary hysteresis nonlinearity (whose characteristics vary under the action of external forces) according to the Krasnosel’skii-Pokrovskii scheme. Sufficient conditions under which the operator is defined for the inputs from the class of functions H 1[t 0, T] satisfying the Lipschitz condition in the segment [t 0, T] are established.